Gerry Godley - Godley, Gerry (Irish Journal of Arts Management and Cultural Policy, 2015)
Gerry Godley, a founder member of the National Campaign for the Arts in Ireland (2008), reflected on the impact that the global economic recession had had on cultural policy and arts practice in Ireland. I’m delighted to be here today and to be part of this forum and I’m looking forward to everything that will unfold, particularly the perspective of artists who are among us.